Strategi Mengenali Motif Khas Kain Tenun Cual Bangka Dengan AHP - Hilyah Magdalena; Hadi Santoso (Faculty of Computer Science, University of Jember, 2016)
Woven fabric cual Bangka currently used as one of the identity of community pride in Bangka Belitung Islands. The specificity of this fart cual fabric interesting to study because of the motives that have similarities with songket palembang. Woven fabric cual Bangka and Palembang songket cloth looks similar because the same cloth-making techniques - both using techniques sungkit. The purpose of this research is how to recognize a particular motif woven fabric cual fart. This research using Analytical Hierarchy Process ( AHP ) to classify some specific motifs that exist in woven fabric cual fart. Experts in the field of woven fabric cual is to inform you that the woven fabric cual farts have tabled motif, motifs or patterns, motifs fabric edge, motif gold thread, fabric base material, as well as the specific color. The research involved four experts that the results of the questionnaires is processed by software Expert Choice 2000. The results showed that the main peculiarity of the woven fabric cual fart is in a pattern or motif with a percentage of 31.5, and is the chosen alternative product is songket with a percentage of 25.4.